2016
DOI: 10.1186/s12888-016-1076-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic relapse and associated factors among patients attending health services in Southwest Ethiopia: a cross-sectional study

Abstract: BackgroundPsychotic relapse leads to repeated hospitalization and negatively affects the clinical prognosis of the patients. Information on prevalence of relapse among patients with psychotic disorders in Ethiopian setting is scarce. This study aimed to assess the prevalence of relapse among patients with psychotic disorders attending services in Jimma University Specialized Hospital (JUSH).MethodsData were collected using interviewer administered questionnaire. We used medication adherence rating scale (MARS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 42 publications
6
36
1
1
Order By: Relevance
“…This study found that non-adherence increase relapse by 6.35 times compared to being adherent which was supported by the study done in the United States of America [36], London [37], India [38], Jordan [39], Jimma [33] and this similar result might be explained by adherence to medication is a pillar for the patient to control symptoms and prevent relapse. This study found that high disability score increases the chance of relapse by 3.72 times compared to having low disability score, and this study finding was supported by the world health organization mental illness prevention report [40], and this supporting evidence might be explained by patients current functionality status including their personal care and participation in a society which contributes for the stigma and self-esteem of patents associated with their current functionality and contribute for relapse.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This study found that non-adherence increase relapse by 6.35 times compared to being adherent which was supported by the study done in the United States of America [36], London [37], India [38], Jordan [39], Jimma [33] and this similar result might be explained by adherence to medication is a pillar for the patient to control symptoms and prevent relapse. This study found that high disability score increases the chance of relapse by 3.72 times compared to having low disability score, and this study finding was supported by the world health organization mental illness prevention report [40], and this supporting evidence might be explained by patients current functionality status including their personal care and participation in a society which contributes for the stigma and self-esteem of patents associated with their current functionality and contribute for relapse.…”
Section: Discussionsupporting
confidence: 72%
“…This study found that lifetime prevalence of relapse70.2% which was higher than the study done in Johannesburg (61.8%) [4], London (53%) [31] and India (70%) [32] and this difference might due to the difference in a study participant, mental health service and literacy. Also, it is higher than the study done in Jimma (24.6%) [33], Addis Ababa (43%) [34] and Butajira (65.9%) [35] and this might be the difference in sample size, study design, and study setting as well as the diagnosis of patients were not inclusive.…”
Section: Discussionmentioning
confidence: 68%
“…The sample size was calculated using a single population proportion formula considering 43.3% relapse [ 19 ], 95% confidence interval, 5% margin of error, and 10% non-response rate. The final sample size was 415.…”
Section: Methodsmentioning
confidence: 99%
“…Another substance abuse was measured using the Drug Abuse Screening Test (DAST-10), which is a 10-item asking about abuse, dependence, and low-risk substance use in the last 12 months. This measure has been included in previous research conducted in Ethiopia [ 19 , 39 41 ]. DAST-10 has a very good internal consistency (α = 0.92), sensitivity, and specificity of 0.98 and 0.91 respectively [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation